Almost Continuity for Multifunctions Defined from an Ideal Topological Space into a Bitopological Space (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new concepts of continuous multifunctions defined between an ideal topological space and a bitopological space, namely upper almost $τ^\star(σ_1,σ_2)$-continuous multifunctions and lower almost $τ^\star(σ_1,σ_2)$-continuous multifunctions. Moreover, several characterizations and some properties concerning upper almost $τ^\star(σ_1,σ_2)$-continuousmultifunctions and lower almost $τ^\star(σ_1,σ_2)$-continuous multifunctions are considered. Furthermore, the relationships between $τ^\star(σ_1,σ_2)$-continuity and almost $τ^\star(σ_1,σ_2)$-continuity are discussed.
Keywords: upper almost $τ^\star(σ_1,σ_2)$-continuous multifunction; lower almost $τ^\star(σ_1,σ_2)$-continuous multifunction